LANGUAGE POLITENESS ON INSTAGRAM: A CASE STUDY OF PUBLIC OFFICER AT JAKARTA, INDONESIA - Hidayat, Noval Nur; Rahman, Fathu; Abas, Asriani (Universitas Khairun, 2023)
Advances in technology at this time not only to open mind but also changed the way humans communicate and interact. Forms of communication that are generally carried out face-to-face have now shifted a lot to virtual forms of communication on social media as intermediaries. Furthermore, communication on social media allows people to speak freely without thinking about language ethics and politeness. This virtual communication not only involves text alone but also uses emotions to represent a picture of their feelings. This research aims to find the use of official language on Instagram social media and to analyze the use of public officials' language when communicating on social media.Ã‚Â The social media chosen as the subject of this study is Instagram which is widely used and accessed by internet users. This research used a descriptive qualitative method. The data source for this research prioritizes uploads by public officials only. The implementation of data collection in this study was a documentation method by collecting uploads of public officials on Instagram social media. The results of this study found that most public officials in private uploads had impolite comments seen in five factors, namely direct criticism with harsh words, encouragement of the speaker's emotional sense, protective of opinions, deliberately accusing the interlocutor, and deliberately cornered speech partners.